Plasticity of the Anemonia viridis microbiota in response to different levels of combined anthropogenic and environmental stresses - Palladino, Giorgia; Rampelli, Simone; Galià-Camps, Carles; Scicchitano, Daniel; Trapella, Giulia; Nanetti, Enrico; Angelini, Valeria; Cleo, Daniela; Turroni, Silvia; Corinaldesi, Cinzia; Candela, Marco (Frontiers in Marine Science, 2022)
Despite their recognized primary importance, marine coastal ecosystems around the globe are currently under threat, being subject to continuous local and global anthropogenic stressors. In this frame, understanding the response of coastal habitat-forming species to multiple stressors and their resilience is fundamental for the sustainable management of coastal ecosystems. In the present study, to provide some glimpses in this direction, we explored the response of the Anemonia viridis-associated microbiota to the combined anthropogenic stressors, which typically affect touristic hotspots at Mediterranean coastal sites. To this aim, two case studies have been carried out, the first in the Riccione coastal site (Italy, Center Mediterranean) and the second at Cap de Creus (Spain, North-western Mediterranean), where the A. viridis microbiota was assessed under the conditions of both high and low anthropogenic pressure. According to our findings, the A. viridis microbiota showed a relevant degree of plasticity in response to combined anthropogenic and environmental stressors, with changes that also mirrored variations in the surrounding seawater, thus indicating a close connection with the environment, from which potential symbiotic partners are selected. However, this potentially adaptive process also has a limitation, as observed in the highly anthropogenic impact site of Cap de Creus, where A. viridis-associated microbiota appeared completely unstructured, as demonstrated by an increased dispersion according to the Anna Karenina principle. This raises the question about the resilience of the A. viridis-associated microbiota under combined climate and anthropogenic threats, as well as of the anthropogenic factors driving the observed dysbiosis changes.